Multicentric Castleman's disease and Kaposi's sarcoma in a cyclosporin treated, HIV-1 negative patient: case report - Bollen, JM (BioMed Central, 2003)
BACKGROUND: Multicentric Castleman's disease (MCD) is a rare disease, but is more frequent in AIDS patients. MCD has only been reported twice before in patients receiving immunosuppressive therapy after renal transplantation, and never in patients receiving immunosuppressive therapy without transplantation. About half of the cases of MCD are human herpesvirus 8 (HHV8) – related, in contrast to Kaposi's sarcoma, a more common complication arising after immunosuppression, where the virus is found in virtually all cases. CASE PRESENTATION: We report a HIV-1 negative, non-transplant patient who developed HHV8-associated multicentric Castleman's disease and Kaposi's sarcoma after 17 years of immunosuppressive treatment with cyclosporin A for a minimal change nephropathy. Chemotherapy with liposomal doxorubicin resolved both symptoms of multicentric Castleman's disease and Kaposi's sarcoma in this patient. A concomitant decline in the HHV8 viral load in serum/plasma, as determined by a quantitative real-time PCR assay, was observed. CONCLUSIONS: Multicentric Castleman's disease can be a complication of cyclosporin A treatment. Both multicentric Castleman's disease and Kaposi's sarcoma in this patient were responsive to liposomal doxorubicin, the treatment of choice for Kaposi's sarcoma at the moment, again suggesting a common mechanism linking both disorders, at least for HHV8-positive multicentric Castleman's disease and Kaposi's sarcoma. HHV8 viral load measurements can be used to monitor effectiveness of therapy.